Budgeting and financial management for national defense - McCaffery, Jerry; Jones, L. R. (Emerald Publishing Limited : Information Age Publishing, 2004)
Budgeting for national defense is a complex endeavor, particularly for a nation like the U.S. that assumes global responsibility and strives to have the most advanced and lethal force on earth. It is necessary - and challenging - to balance the myriad requirements between current and future readiness, across warfare areas and military services, between having state of the art capability with sufficient capacity, and among people, hardware, and the activities people do with that hardware. As analytically difficult as that problem is, it is embedded in the political budgeting processes and national security must be balanced with every other function of government and there must also be cooperation across branches of government. This text explores that complex endeavor.
Keywords: Budget -- United States.; United States -- Armed Forces -- Appropriations and expenditures.; Military readiness.; History -- Military -- Strategy.; Military and defence strategy.; Military history.; elektronické knihy; electronic books